1983
DOI: 10.3727/036012983816715019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupuncture on Blood Pressure: The Interrelation of Sympathetic Activity and Endogenous Opioid Peptides

Abstract: Experimental hypertension was produced by intravenous infusion of norepinephrine in 13 conscious dogs. Electroacupuncture at the dogs' "Tsu San-Li" (St. 36) points showed a significant decrease in blood pressure, while the heart rate was not affected. The depressor effect was naloxone (0.2 mg/kg iv) reversible, and accompanied by an increased blood flow at the mesenteric artery, so it is suggested that the depressor effect was due to inhibition of the sympathetic vasoconstrictor tone. This inhibition was media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The exact involvement of the opioid pathway was not investigated in the present study. It is possible that EA may activate central opioids that inhibit the sympathetic outflow, resulting in vagal dominance (15,22).…”
Section: Discussionmentioning
confidence: 99%
“…The exact involvement of the opioid pathway was not investigated in the present study. It is possible that EA may activate central opioids that inhibit the sympathetic outflow, resulting in vagal dominance (15,22).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent renewal of interest in the inhibitory effects of electroacupuncture of the Zusanli acupoint on the cardiovascular system, including reductions in arterial pressure (AP), heart rate, (3,15,16), and sympathetic nerve activity (SNA) (25,42). Such inhibitory effects are observed during lowfrequency (Ͻ20 Hz) electroacupuncture.…”
mentioning
confidence: 99%
“…arterial pressure; equilibrium diagram ALTHOUGH THERE ARE MANY clinical case reports (21,30,32,39,40,42), the effects of electroacupuncture on cardiovascular regulation remain to be systematically investigated. There has been a recent renewal of interest in the inhibitory effects of electroacupuncture of the Zusanli acupoint on the cardiovascular system, including reductions in arterial pressure (AP), heart rate, (3,15,16), and sympathetic nerve activity (SNA) (25,42). Such inhibitory effects are observed during lowfrequency (Ͻ20 Hz) electroacupuncture.…”
mentioning
confidence: 99%
“…It remains unclear whether EA at ST-36 itself affects MAP (43). We have recently shown that EA at ST-36 has no effects on MAP in healthy humans (44).…”
Section: Discussionmentioning
confidence: 98%